Help-Seeking Behaviour of Men in Regards to Lower Bowel Symptoms - Oberoi, Devesh Varun (Curtin University, 2015)
Lower bowel symptoms are common and may mimic colorectal cancer. Men have a higher risk of cancer but are reticent to seek medical help. This study aimed to explore the help seeking behaviour of men in regards to lower bowel symptoms. Quantitative survey and exploratory qualitative studies were conducted and several barriers and facilitators to help-seeking were identified. This result represents a trajectory of help seeking from symptoms to the diagnosis of colorectal disease.